A comparison of the McGrath® Series 5 videolaryngoscope and Macintosh laryngoscope for double‐lumen tracheal tube placement in patients with a good glottic view at direct laryngoscopy. (27th February 2015) - Yao, W. L.; Wan, L.; Xu, H.; Qian, W.; Wang, X. R.; Tian, Y. K.; Zhang, C. H.
Summary We compared the McGrath® Series 5 videolaryngoscope with the Macintosh laryngoscope for double‐lumen tracheal tube placement in patients with a predicted good glottic view on assessment of the airway. An initial laryngoscopy was performed using the Macintosh laryngoscope; 96 patients with Cormack and Lehane grade‐1 or ‐2a views were randomly assigned to undergo intubation using either the McGrath or Macintosh device. Compared with the Macintosh laryngoscope, the McGrath videolaryngoscope provided more Cormack and Lehane grade‐1 views (47 (97.9%) vs 29 (60.4%), p < 0.05), a longer mean (SD) intubation time (39.6 (10.0) s vs 24.4 (7.3) s, p < 0.05) and a higher incidence of double‐lumen tube malposition (6 (12.5%) vs 0, p < 0.05). However, in 18 non‐randomised patients with Cormack and Lehane grade ≥ 2b on initial laryngoscopy using the Macintosh, the glottic view was improved on intubation with the McGrath videolaryngoscope, with a total success rate of double‐lumen tube placement of 94.4% and mean (SD) intubation time of 50.0 (18.6) s. We recommend that in patients with a low airway risk index score requiring intubation with a double‐lumen tracheal tube, the Macintosh laryngoscope is used as the first device and the McGrath videolaryngoscope is used only if this provides a poor glottic view.